2015
DOI: 10.1111/bjh.13298
|View full text |Cite
|
Sign up to set email alerts
|

MDX‐1097 induces antibody‐dependent cellular cytotoxicity against kappa multiple myeloma cells and its activity is augmented by lenalidomide

Abstract: SummaryMDX-1097 is an antibody specific for a unique B cell antigen called kappa myeloma antigen (KMA) that consists of cell membrane-associated free kappa light chain (jFLC). KMA was detected on kappa human multiple myeloma cell lines (jHMCLs), on plasma cells (PCs) from kappa multiple myeloma (jMM) patients and on jPC dyscrasia tissue cryosections. In primary jMM samples, KMA was present on CD38+ cells that were CD138 and CD45 positive and/or negative. MDX-1097 exhibited a higher affinity for KMA compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…MDX-1097 binds to serum κ FLC (κFLC), albeit with lower affinity than to malignant MM cells, and importantly, KMA is not found on normal human leucocytes 68 . KMA is non-covalently associated with lipids in the plasma membrane and MDX-1097 binding to KMA may induce changes to the cell membrane, potentially activating immune cell signal transduction pathways 7 . Further, our in vitro studies demonstrated that MDX-1097 induces ADCC and this effect is augmented in the presence of lenalidomide 7 .…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…MDX-1097 binds to serum κ FLC (κFLC), albeit with lower affinity than to malignant MM cells, and importantly, KMA is not found on normal human leucocytes 68 . KMA is non-covalently associated with lipids in the plasma membrane and MDX-1097 binding to KMA may induce changes to the cell membrane, potentially activating immune cell signal transduction pathways 7 . Further, our in vitro studies demonstrated that MDX-1097 induces ADCC and this effect is augmented in the presence of lenalidomide 7 .…”
Section: To the Editormentioning
confidence: 99%
“…KMA is non-covalently associated with lipids in the plasma membrane and MDX-1097 binding to KMA may induce changes to the cell membrane, potentially activating immune cell signal transduction pathways 7 . Further, our in vitro studies demonstrated that MDX-1097 induces ADCC and this effect is augmented in the presence of lenalidomide 7 . Given that KMA is expressed on malignant B cells, we feel that this mAb has therapeutic potential for treating MM.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…81 In mice studies, both anti-PD-1 and anti-cytotoxic T-lymphocyteassociated antigen-4 (CTLA-4) antibodies were unable to eradicate large, modestly immunogenic CT26 tumours or metastatic 4T1 tumours. …”
Section: Epigenetic Therapies In Combination With Monoclonal Antibodiesmentioning
confidence: 99%